Work, rights and collective organization in the 21st century (April-June, 2025) - Arguedas Abarca, María Fernanda (2025)
Within the thematic axis “Work, Rights and Collective Organization in the 21st Century,” the selected articles examine contemporary transformations in the world of work from multiple perspectives. Senén and Escudero analyze innovative union strategies developed by Argentina’s Frente Sindical de Acción Climática in response to rapid technological and climate transitions, highlighting initiatives such as telework collective agreements, digital-platform worker representation, and climate-focused training programs. Pineda studies artivism as a feminist, anti-racist and labor tool within Sindihogar in Barcelona, showing how embroidery, performance, and dance function as practices of political denunciation, collective knowledge-making, and emotional community-building. Sabillón explores the severe precariousness faced by care workers in Honduras—extremely low wages, lack of labor rights, and pervasive informality—calling for urgent public policies that recognize and protect this essential work. Finally, Monreal-Torres, Barragán-Perea and González-Quiñones analyze teacher burnout resulting from the shift to virtual education during the COVID-19 pandemic, underscoring digital stress, work overload, and the need for institutional prevention strategies. Together, these articles provide a critical overview of 21st-century labor challenges and emerging forms of organization, resistance, and care.